MACHIAVELLIAN, MONEY ETHIC DAN NIAT MELAKUKAN PENGHINDARAN PAJAK : RELIGIUSITAS SEBAGAI PEMODERASI: MACHIAVELLIAN, MONEY ETHIC AND INTENTION TO DO TAX EVASION : RELIGIOSITY AS A MODERATION - Prasetyatini, Sri Lestari Yuli; Handeri, Handeri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The purpose of this study was to determine the effect of machiavellian and money ethics with religiosity as a moderator on the intention to carry out tax evasion. This type of research is quantitative. Primary data is used to collect data by distributing questionnaires to Yogyakarta taxpayers. The sampling technique in this study was purposive sampling. Data collection was carried out by distributing the Google Form link via WhatsApp social media. The number of questionnaires processed was 100 respondents. The results of this study indicate that machiavellian has a positive effect on tax evasion intentions, money ethics has no effect on tax evasion intentions, religiosity moderates the machiavellian effect on tax evasion intentions, and religiosity does not moderate the effect of money ethics on tax evasion intentions.